Passive solar tracking system for designing on-grid solar power plant projects - Tang , Huệ Hưng; Nguyen , Văn Hiếu (Journal of Technical Education Science, 2016)
Solar tracking method is one of the methods to help improve the obtained energy for solar power system. It has been applied in many developed countries, but not yet widely used in Vietnam. In this study, the authors focused on design and manufacture of a solar tracking method based on latitude, longitude and time. The authors synthesized methods for determining the exact angle of the sun, thus manufactured and built an algorithm for tracking system; experimentally measured and compared the obtained energy of solar power systems between tracking and fixed installation systems in different weather conditions. Then the effectiveness of solution was analyzed when it would be applied in Vietnam. The experimental results showed that the solution brought back advantages and helped increase 30% obtained energy compared to a non-tracking system. In addition, software to help users calculate and design solar on-grid system based on location throughout Vietnam was developed. With the ability to help improve efficiency for solar power systems, this tracking solution can help reduce total capacity of solar project, investment costs and save materials. It is very applicable in Vietnam. In particular, with developing technology, the higher efficiency the solar panel will have, the more meaningful contribution of the tracking solution will be promoted.